2022
DOI: 10.1002/adom.202201834
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Silicon Quantum Dot‐Based Cavity Light‐Emitting Diodes with Narrowed and Tunable Electroluminescence

Abstract: the alternatives, [7] Si is attractive because of its abundance, biocompatibility, [8] compatibility with silicon-based electronics, [9] luminescent properties when formed as QDs and established/tailorable surface chemistry. [10] EL of silicon-based nanomaterials (e.g., porous silicon, [11] Si nanocrystals in solid matrices [12] ) was first reported in the early 1990s and 2000s with low external quantum efficiencies (EQE) from 10 −6 to 1%. Of late, attention has shifted to colloidal silicon quantum dots (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…In contrast, Cheong et al (2022) 95 recently demonstrated that the electroluminescence of colloidal SiQD particles with narrow emission in the range of B100-23 nm at visible light wavelengths (yellow, orange, red to infrared) could be tuned without changing the dimensions of the SiQD particles. 95 Emission narrowing was achieved solely by adjusting the Fabry-Pe ´rot cavities, and the voltage applied. The results show that the visual and spectral stability is remarkable at different voltages.…”
Section: View Article Onlinementioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, Cheong et al (2022) 95 recently demonstrated that the electroluminescence of colloidal SiQD particles with narrow emission in the range of B100-23 nm at visible light wavelengths (yellow, orange, red to infrared) could be tuned without changing the dimensions of the SiQD particles. 95 Emission narrowing was achieved solely by adjusting the Fabry-Pe ´rot cavities, and the voltage applied. The results show that the visual and spectral stability is remarkable at different voltages.…”
Section: View Article Onlinementioning
confidence: 96%
“…There are many methods have been developed to produce hydrogen-terminated SiQDs. It is worth to mentions: silane gas plasma synthesis (SiH 4 ), 22,23,25,88,89 electrochemical etching, [90][91][92] halosilane reduction reaction, 93,94 oxide-rich silicon thermal synthesis, [53][54][55] hydrogen silsesquioxane thermal synthesis, 4,6,11,17,[29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51][52]95 tetraethoxysilane (TES) thermal synthesis, 96,97 pulsed laser ablation, and recently also the green synthesis of rice husk thermal pyrolysis. 85 In general, the photoluminescence of the resulting material depends on the type of synthesis carried out.…”
Section: B Hydrogen Terminated Siqd Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the PL emission, the PSi has been extensively studied due to its unique characteristics, such as its wide specific area in a small volume, pore size control, biocompatibility, and its compatibility with silicon manufacturing technologies [ 2 , 3 , 4 , 5 , 6 ]. There are numerous techniques for processing crystalline silicon and to obtain the Psi.…”
Section: Introductionmentioning
confidence: 99%